2003
DOI: 10.1038/sj.ijo.0802387
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin levels do not change with moderate dietary induced weight loss and exercise in obese postmenopausal women

Abstract: OBJECTIVE:The purpose of this study was to determine changes in adiponectin levels with moderate weight loss, weight loss plus aerobic exercise, or weight loss plus resistive exercise in overweight and obese, sedentary postmenopausal women. DESIGN: Longitudinal, clinical intervention study of 6-month (3 Â /week) program of either weight loss (WL, n ¼ 15), weight loss + aerobic exercise (WL+AEX, n ¼ 16), or weight loss + resistive exercise (WL+RT, n ¼ 9) SUBJECTS: We studied 40 sedentary, overweight and obese (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
107
2
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(122 citation statements)
references
References 22 publications
10
107
2
3
Order By: Relevance
“…Training studies have shown that exercise might not be a significant factor towards adiponectin modifications (Marcell et al 2005;Ryan et al 2003). It seems that modifications in body weight or body composition might be responsible for alterations in adiponectin levels (Esposito et al 2003;Hulver et al 2002;Monzillo et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Training studies have shown that exercise might not be a significant factor towards adiponectin modifications (Marcell et al 2005;Ryan et al 2003). It seems that modifications in body weight or body composition might be responsible for alterations in adiponectin levels (Esposito et al 2003;Hulver et al 2002;Monzillo et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that basal adiponectin concentration was not altered after longterm exercise [10][11][12][13][14]. In contrast, Kriketos et al [15] recently reported that fasting adiponectin levels increased by 260% above baseline values after 2-3 bouts of low to moderate intensity exercise.…”
mentioning
confidence: 97%
“…Several studies exploring the effects of exercise on circulating adiponectin levels have resulted in inconsistent findings [10][11][12][13][14][15]. It has been shown that basal adiponectin concentration was not altered after longterm exercise [10][11][12][13][14].…”
mentioning
confidence: 99%
“…29,34,[45][46][47][48][49][50][51][52][53][54][55] Female data were compiled from 15 studies (26 groups of individuals), with study sample size ranging from 8 to 662 individuals and a mean sample size of 94. 29,45,46,48,50,[53][54][55][56][57][58][59][60][61][62] Lack of BMI-adiponectin association S-M Kuo and MM Halpern Among these studies, eight studies included subjects of both genders and the measurements from men and women were reported separately. The sample size as well as the age and BMI profiles of these studies are summarized in Table 1.…”
Section: Data Collectionmentioning
confidence: 99%
“…The regression analysis of female adiponectin to leptin was based on data from 13 groups 45,50,53,54,56,58,61,62 and Pearson's correlation was 0.37 (P40.05, not significant). The analysis confirmed the expected lack of correlation between adiponectin and leptin in healthy individuals.…”
Section: Lack Of Bmi-adiponectin Association S-m Kuo and MM Halpernmentioning
confidence: 99%